2010
DOI: 10.1016/j.cmet.2010.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Rim2α Determines Docking and Priming States in Insulin Granule Exocytosis

Abstract: Insulin secretion is essential for maintenance of glucose homeostasis, but the mechanism of insulin granule exocytosis, the final step of insulin secretion, is largely unknown. Here, we investigated the role of Rim2alpha in insulin granule exocytosis, including the docking, priming, and fusion steps. We found that interaction of Rim2alpha and Rab3A is required for docking, which is considered a brake on fusion events, and that docking is necessary for K(+)-induced exocytosis, but not for glucose-induced exocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
119
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 48 publications
3
119
0
Order By: Relevance
“…4a, b). 'Newcomer SGs' were new SGs appearing de novo under an evanescent field after stimulation and then underwent exocytosis, appearing in two distinct patterns as described previously [4,10,19,23]: 'no-dock' newcomer SGs (shown in white in Fig. 4a, b) were newly recruited by stimulation and immediately fused with PM (docking state of<200 ms, the minimal interval between two consecutive frames); 'short-dock' newcomer SGs (shown in grey in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4a, b). 'Newcomer SGs' were new SGs appearing de novo under an evanescent field after stimulation and then underwent exocytosis, appearing in two distinct patterns as described previously [4,10,19,23]: 'no-dock' newcomer SGs (shown in white in Fig. 4a, b) were newly recruited by stimulation and immediately fused with PM (docking state of<200 ms, the minimal interval between two consecutive frames); 'short-dock' newcomer SGs (shown in grey in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We had alternatively postulated that reduced levels of the SM-SNARE complex comprised of Munc18a, Syn-1A, SNAP25 and VAMP2 in beta cells contributed to the defective exocytosis of pre-docked insulin SGs in islets of individuals with type 2 diabetes [29,30]. More recent work showed that newcomer SGs contributed to primary exocytosis [4,5,23], and in fact far exceeded pre-docked SGs in the overall GSIS [5]. Remarkably, these newcomer SGs are recruited to the PM to undergo exocytosis with minimal to no residence time on the PM [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…'Newcomer SGs' were new SGs appearing de novo under evanescent field after stimulation and which then underwent exocytosis. Newcomer SGs could be further categorised into two distinct patterns as described previously [5,7,24], designated as 'no-dock' (middle, Fig. 3d) and 'short-dock' (bottom, Fig.…”
Section: Syn-3 Is a T-snare On Sgsmentioning
confidence: 99%
“…We found 29 different putative Rab37-binding proteins that might be involved in TNF-a secretion from macrophages (Supporting Information Table S1). One, Munc13-1, has a functional interaction with Rab3A-interacting molecule 2 (RIM2) in the final step of exocytosis and is essential for insulin secretion from islet b cells [22].…”
Section: Identification Of the Rab37-binding Proteinmentioning
confidence: 99%
“…We found 29 different putative Rab37-binding proteins that might be involved in TNF-a secretion from macrophages (Supporting Information Table S1). One, Munc13-1, has a functional interaction with Rab3A-interacting molecule 2 (RIM2) in the final step of exocytosis and is essential for insulin secretion from islet b cells [22].Using immunofluorescence staining, we determined that Munc13-1 colocalized with both EGFP-Rab37 and TNF-a in LPSstimulated RAW264.7 macrophages ( Fig. 5C; 76.375.4% n 5 18 and D; 73.878.3% n 5 18 cells), suggesting that Munc13-1 is associated with Rab37-bound TNF-a-containing vesicles in activated macrophages.…”
mentioning
confidence: 99%